Retroperitoneal Extraskeletal Mesenchymal Chondrosarcoma: A Very Rare Case Report - Koc, Mustafa; Ozercan, Mehmet Resat (Aves, 2016)
Chondrosarcoma is an uncommon malignant neoplasm of cartilaginous origin. Extraskeletal chondrosarcomas are far less common than their intraosseous counterparts, representing approximately 2% of all soft tissue sarcomas. Clinically, extraskeletal mesenchymal chondrosarcoma (EMC) shows a very fast progression. It also has a high incidence of local recurrence and distant metastasis. The most common locations are the bladder, brain, meninges, mediastinum, and thighs. Other sites, including the retroperitoneum, are very uncommon. The diagnosis of mesenchymal chondrosarcoma can be very challenging, particularly in cases without conspicuous cartilaginous differentiation. In such cases, its distinction from other neoplasms cannot be safely established. Here we present a retroperitoneal tumor diagnosed as EMC in a 73-year-old female.
Keywords: Chondrosarcoma; multidetector computed tomography; retroperitoneal